Military Conflicts and Education - العيسـى فادي (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Education in general is facing many problems, let alone adding conflict and terrorism to the situation to make the process more complicated for both teachers and students. In order for teaching to be effective, the classroom has to be a safe place for sharing experiences and finding healing during times of risk, conflict, and controversy. This research aims at synthesizing knowledge about education in countries with military conflicts. It focuses on exploring the empirical and professional literature to reveal what we know about education during times of military conflict. The intention is to examine how these programs have been studied.